Sir David Cecil Smith. 21 May 1930—29 June 2018. (14th December 2019) - Douglas, Angela E.
Abstract : David Smith was an international authority in the biological discipline of symbiosis and an influential leader in academic life. Through his work on photosynthetic symbioses in lichens and invertebrate animals, David transformed the field of symbiosis from a study of taxonomy and morphology into an experimental science. In particular, he applied novel radiotracer techniques to demonstrate that lichens are metabolically dynamic, with photosynthetically-fixed carbon transferred from symbionts to lichen host at high rates. His subsequent study of diverse symbioses led him to develop common principles underlying symbioses, including the regulated transfer of metabolites between partners and the role of ecological processes of colonization and community assembly in the establishment of symbioses. In his academic service, David had multiple leadership roles, including head of the Department of Botany at University of Bristol (1974–1980), head of the Department of Agricultural Science at University of Oxford (1980–1987), principal of University of Edinburgh (1987–1994) and president of Wolfson College, University of Oxford (1994–2000). David was biological secretary of the Royal Society (1983–1987) and he was knighted in 1986.